2020
DOI: 10.1007/s40519-020-00883-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of dietary acid load with anthropometric indices in children and adolescents

Abstract: Purpose High dietary acid load (DAL) may have an influence on anthropometric indices. Given that there was no study on the association between DAL and anthropometric indices children and adolescents, the current study was aimed to examine the association between DAL and anthropometric indices in Iranian children and adolescents. Methods Students aged 6-18 years were recruited using a multi-stage, cluster sampling method from 30 provinces of Iran. Dietary intake was assessed through a validated food frequency q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
0
7
0
2
Order By: Relevance
“…A population-based cross-sectional study among 5326 Iranian children and adolescents (6–18 years) demonstrated a direct association between the neck circumference, an index of upper subcutaneous adipose tissue distribution, and NEAP. However, this study failed to show any association between the NEAP and PRAL with other anthropometric measures [ 15 ]. Similarly, another cross-sectional study among 1136 young Japanese women (18–22 years) revealed a positive association between DAL, estimated as the ratio of dietary protein to K (Pro: K), with BMI and waist circumference [ 23 ].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A population-based cross-sectional study among 5326 Iranian children and adolescents (6–18 years) demonstrated a direct association between the neck circumference, an index of upper subcutaneous adipose tissue distribution, and NEAP. However, this study failed to show any association between the NEAP and PRAL with other anthropometric measures [ 15 ]. Similarly, another cross-sectional study among 1136 young Japanese women (18–22 years) revealed a positive association between DAL, estimated as the ratio of dietary protein to K (Pro: K), with BMI and waist circumference [ 23 ].…”
Section: Discussionmentioning
confidence: 95%
“…For example, a large cross-sectional study showed that NEAP was positively associated with neck circumference in students aged 6–18 years. Also, higher PRAL and NEAP were associated with lower body mass index (BMI) in parents [ 15 ]. In addition, findings from another study revealed that there was no association between PRAL and anthropometric measures in 6-year-old girls [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, another study found the same finding in adults, but higher scores of NEAP were associated with increased risk of impaired fasting blood glucose 37 . A national multi-center cross-sectional survey on 5326 Iranian students aged 6–18 years after evaluating anthropometric indices, showed a direct association between diet-induced acid load with neck circumference 23 . Furthermore, an inverse relationship was found between DAL indices and parental BMI 23 .…”
Section: Discussionmentioning
confidence: 99%
“…A national multi-center cross-sectional survey on 5326 Iranian students aged 6–18 years after evaluating anthropometric indices, showed a direct association between diet-induced acid load with neck circumference 23 . Furthermore, an inverse relationship was found between DAL indices and parental BMI 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation